Bicara Merdeka to inculcate the love for the country - Nor Hidayah, Mohamad (2017)
More than 500 staff and students attended Bicara Merdeka Program organized by Registry Department in conjunction with the Celebration of Merdeka Months and Malaysia Day 2017 held at Astaka Hall, UMP Gambang Campus